1001 Little Ways to Look Younger - Baxter-Wright, Emma; Illustrated by Morley, Carol (London Carlton Book, 2008)
From age-defying makeup tricks and fashion tips to cosmetic procedures and skincare advice, this title includes solutions for wrinkles, as well as advice on topics ranging from improving your memory to battling the effects of ageing on the body. It shows both preventative and curative ways to stay young, beautiful and physically fit
Include Illustrations and Index
Keywords: Aging--Prevention -- Beauty, Personal